Regulação do crédito bancário e desenvolvimento local: o debate sobre os resultados do Community Reinvestment Act dos Estados Unidos - Oliveira, Fabiana Franco de (2009)
This paper seeks to analyze the debate on the results of the american local reinvestment law Community Reinvestment Act (CRA), aimed at the role of government regulating in expanding access to credit, as well its participation in local development. At the height of the Great Depression in the 1930s, the funding program for housing in the New Deal had as objective to create jobs for thousands of unemployed. The mortgage of the government, however, has not benefited everyone. A large inventory was designed to assess the residential areas of the country. The mapping of regions where the banks could not provide loans worth up to discriminatory criteria. The factors of exclusion had nothing to do with the solvency of the inhabitants, but with the conservation status of the neighborhoods and the presence of ethnic minorities on the spot. The practice was called redlining because the areas excluded from access to credit were red delineated on the maps prepared by the government. Researchers of urban planning in the United States argue that these maps were used by public and private entities to, years later, denying loans to people in black communities or low-income neighborhoods. The assumptions of redlining resulted in increasing the geographical and racial segregation and has contributed to urban decay. The CRA was created in 1977 to combat redlining in the granting of mortgage financing. While the immediate goal was to punish discrimination in the granting of loans, the issue of local economic development has been the more comprehensive target of the law. After 30 years of implementation, what were the results? Based on analysis of existing literature on the impact of CRA on access to credit for low-income communities and ethnic minorities, this study seeks answers to these questions. The object of this debate analysis also houses the controversy surrounding the relationship between the CRA and the credit crisis linked to the U.S. mortgage system